Molecular systematics of two sister clades, the Fusarium concolor and F. babinda species complexes, and the discovery of a novel microcycle macroconidium–producing species from South Africa. (2nd November 2018) - Jacobs-Venter, Adriaana; Laraba, Imane; Geiser, David M.; Busman, Mark; Vaughan, Martha M.; Proctor, Robert H.; McCormick, Susan P.; O'Donnell, Kerry
ABSTRACT: Multilocus DNA sequence data were used to investigate species identity and diversity in two sister clades, the Fusarium concolor (FCOSC) and F. babinda species complexes. Of the 109 isolates analyzed, only 4 were received correctly identified to species and these included 1/46 F. concolor, 1/31 F. babinda, and 2/3 F. anguioides . The majority of the F. concolor and F. babinda isolates were received as F. polyphialidicum, which is a heterotypic synonym of the former species. Previously documented from South America, Africa, Europe, and Australia, our data show that F. concolor is also present in North America. The present study expands the known distribution of F. babinda in Australia to Asia, Europe, and North America. The molecular phylogenetic results support the recognition of a novel Fusarium species within the FCOSC, which is described and illustrated here as F. austroafricanum, sp. nov. It was isolated as an endophyte of kikuyu grass associated with a putative mycotoxicosis of cattle and from plant debris in soil in South Africa. Fusarium austroafricanum is most similar morphologically to F. concolor and F. babinda but differs from the latter two species in producing (i) much longer macroconidia in which the apical cell is blunt to slightly papillate and the basal cell is only slightly notched and (ii) macroconidia via microcycle conidiation on water agar. BLASTn searches of the whole genome sequence of F. austroafricanum NRRL 53441 were conducted to predict mycotoxin potential, using genes known to be essential for the synthesis of several mycotoxins and biologically active metabolites. Based on the presence of intact gene clusters that confer the ability to synthesize mycotoxins and pigments, we analyzed cracked corn kernel cultures of F. austroafricanum via liquid chromatography–mass spectrometry (LC-MS) but failed to detect these metabolites in vitro.